LEVEL OF KNOWLEDGE, INTEREST, AND PERCEPTION OF CLINICAL ROTATION STUDENTS REGARDING FORENSIC MEDICINE AND MEDICOLEGAL SCIENCE - Taufik Suryadi Ismail; Vera Dewi Mulya; Fathin Hidayah (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Forensic medicine and medicolegal science (FMMS) as mandatory competences that clinical rotation students must possess. However, the number of forensic medicine and medicolegal specialists is still significantly less. Currently, there are 271 people recorded and spread across Indonesia, including two people in Aceh Province with three medical faculties to be managed. For this reason, it is necessary to think about how to increase the number of forensic medicine and medicolegal specialists in Aceh. This study describes the level of knowledge, interest, and perceptions of clinical rotation students regarding FMMS.Methods: The type of study was observational analytic with a cross-sectional design. The instrument used was an online questionnaire with a Content Validity Ratio of 0.750. The samples of this study were clinical rotation students who had passed the forensic medicine and medicolegal sciences stages. The samples were collected using the purposive sampling method.Results: A total of 102 respondents were involved in this study. The majority of respondents had good knowledge (97.1%). As many as 63.7% of respondents were interested in studying forensic medicine and medicolegal and 59.8% of respondents positively perceived these studies. Based on the Spearman’s statistical test showed a significant correlation between the interest and perception under the Sig.(2-tailed) 0.002 (Sig.(2-tailed) ≤0.05).Conclusion: Clinical rotation students of the Faculty of Medicine, Syiah Kuala University have good knowledge, high interest, and positive perceptions. This is a new opportunity and challenges for the development of FMMS in Indonesia.